2018
DOI: 10.1111/jpn.13037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term microalgae supplementation on muscle microstructure, meat quality and fatty acid composition in growing pigs

Abstract: We investigated the effects of long‐term microalgae supplementation (7% in a piglet diet and 5% in a fattening diet) on muscle microstructure and meat quality, including fatty acid composition in female Landrace pigs (n = 31). The major effects were muscle‐specific increases in n‐3 and n‐6 polyunsaturated fatty acids (PUFA) concentrations, resulting in increased accumulation of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Carcass traits and meat quality of longissimus thoracis muscle were not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 40 publications
(69 reference statements)
4
47
0
Order By: Relevance
“…Concomitant with the increases of total n-3 PUFA in breast and thigh, the total n-6 PUFA contents (especially LNA and ARA) linearly decreased with MA supplementation. Our results are in accordance with several recent reports on pigs and broilers with MA supplementation [22,23]. The reduction in n-6 PUFA contents probably resulted from the competition of substrates and biosynthesis enzymes between the n-3 and n-6 PUFAs [24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concomitant with the increases of total n-3 PUFA in breast and thigh, the total n-6 PUFA contents (especially LNA and ARA) linearly decreased with MA supplementation. Our results are in accordance with several recent reports on pigs and broilers with MA supplementation [22,23]. The reduction in n-6 PUFA contents probably resulted from the competition of substrates and biosynthesis enzymes between the n-3 and n-6 PUFAs [24].…”
Section: Discussionsupporting
confidence: 93%
“…The significant reduction in WHC during refrigerated storage might be due to the oxidative degradation of membrane phospholipids, which damages the structure and function of membranes and increases the loss of sarcoplasmic fluid [41]. On the contrary, previous studies indicated that MA supplementation decreased the drip loss of meat in broilers [7] and pigs [23]. This phenomenon was explained by low levels of n-3 PUFA enrichment that enabled the muscular cells to build a flexible lipid bilayer membrane, and thus resulting in an increased WHC.…”
Section: Discussionmentioning
confidence: 98%
“…The observed insignificant changes in SFA and MUFA concentration in breast muscles of birds fed studied microalgae diets compared to control were in agreement with previous published reports in animals [42,47,48]. On the other hand, the detected significant increase in the levels of EPA, DHA, n-3 FA, PUFA, and arachidonic acid in breast muscle of broilers chickens fed SP and AC compared to those of birds fed CV and control birds was consistent with and supported by the previous published data in animals [49] and broiler chickens [50,51]. The analysis of fatty acids of studied microalgae indicated that the fatty acid profile in the microalgae differed than that estimated in meat (Table 1).…”
Section: Effect Of Dietary Microalgae On Profiles Of Fatty and Amino supporting
confidence: 93%
“…In general, this study demonstrated that the use of LB Gb and LB Gh additives in gilthead seabream diets does not affect growth and improve feed efficiency. Different positive effects of microalgae products in feeds have been achieved at low level of supplementation such as 5% in salmon 77 , 5–7% in pigs 78 , and only 0.1–0.2% in broiler chicks 29 . In our study, it was found that LB Gb and LB Gh exerted their positive, although different, effects at 0.5–1% in gilthead seabream juveniles.…”
Section: Discussionmentioning
confidence: 99%